Pañjābī kahāṇī : nawīna prawiratīāṃ - Siṅgala, Dharama Pāla; Guralāla Siṅgha (Pañjābī Wibhāga, Gurū Nānaka Dewa Yūnīwarasiṭī Rījanala Saiṇṭara, 1982)
Articles on new trends in the Panjabi short story.